The Lateralization of Motor Cortex Activation to Action-Words - Hauk, Olaf; Pulvermuller, Friedemann (Frontiers in Human Neuroscience, 2011)
What determines the laterality of activation in motor cortex for words whose meaning is related to bodily actions? It has been suggested that the neuronal representation of the meaning of action-words is shaped by individual experience. However, core language functions are left-lateralized in the majority of both right- and left-handers. It is still an open question to what degree connections between left-hemispheric core language areas and right-hemispheric motor areas can play a role in semantics. We investigated laterality of brain activation using fMRI in right- and left-handed participants in response to visually presented hand-related action-words, namely uni- and bi-manual actions (such as “throw” and “clap”). These stimulus groups were matched with respect to general (hand-) action-relatedness, but differed with respect to whether they are usually performed with the dominant hand or both hands. We may expect generally more left-hemispheric motor cortex activation for hand-related words in both handedness groups, with possibly more bilateral activation for left-handers compared to right-handers. In our study, both participant groups activated motor cortex bilaterally for bi-manual words. Interestingly, both groups also showed a left-lateralized activation pattern to uni-manual words. We argue that this reflects the effect of left-hemispheric language dominance on the formation of semantic brain circuits on the basis of Hebbian correlation learning.